Transdermal Delivery of Therapeutic Compounds With Nanotechnological Approaches in Psoriasis - Li, Ning; Qin, Yeping; Dai, Dan; Wang, Pengyu; Shi, Mingfei; Gao, Junwei; Yang, Jinsheng; Xiao, Wei; Song, Ping; Xu, Ruodan (Frontiers in Bioengineering and Biotechnology, 2022)
Psoriasis is a chronic, immune-mediated skin disorder involving hyperproliferation of the keratinocytes in the epidermis. As complex as its pathophysiology, the optimal treatment for psoriasis remains unsatisfactorily addressed. Though systemic administration of biological agents has made an impressive stride in moderate-to-severe psoriasis, a considerable portion of psoriatic conditions were left unresolved, mainly due to adverse effects from systemic drug administration or insufficient drug delivery across a highly packed stratum corneum via topical therapies. Along with the advances in nanotechnologies, the incorporation of nanomaterials as topical drug carriers opens an obvious prospect for the development of antipsoriatic topicals. Hence, this review aims to distinguish the benefits and weaknesses of individual nanostructures when applied as topical antipsoriatics in preclinical psoriatic models. In view of specific features of each nanostructure, we propose that a proper combination of distinctive nanomaterials according to the physicochemical properties of loaded drugs and clinical features of psoriatic patients is becoming a promising option that potentially drives the translation of nanomaterials from bench to bedside with improved transdermal drug delivery and consequently therapeutic effects.